Dietary Compounds as Epigenetic Modulating Agents in Cancer - Carlos-Reyes, Ángeles; López-González, José Sullivan; Meneses-Flores, Manuel; Gallardo-Rincón, Dolores; Ruíz-García, Erika; Marchat, Laurence A.; Astudillo-de la Vega, Horacio; Hernández de la Cruz, Olga N.; López-Camarillo, César (Frontiers in Genetics, 2019)
Epigenetic mechanisms control gene expression during normal development and their aberrant regulation may lead to human diseases including cancer. Natural phytochemicals can largely modulate mammalian epigenome through regulation of mechanisms and proteins responsible for chromatin remodeling. Phytochemicals are mainly contained in fruits, seeds, and vegetables as well as in foods supplements. These compounds act as powerful cellular antioxidants and anti-carcinogens agents. Several dietary compounds such as catechins, curcumin, genistein, quercetin and resveratrol, among others, exhibit potent anti-tumor activities through the reversion of epigenetic alterations associated to oncogenes activation and inactivation of tumor suppressor genes. In this review, we summarized the actual knowledge about the role of dietary phytochemicals in the restoration of aberrant epigenetic alterations found in cancer cells with a particular focus on DNA methylation and histone modifications. Furthermore, we discussed the mechanisms by which these natural compounds modulate gene expression at epigenetic level and described their molecular targets in diverse types of cancer. Modulation of epigenetic activities by phytochemicals will allow the discovery of novel biomarkers for cancer prevention, and highlights its potential as an alternative therapeutic approach in cancer.